Horace's Archytas Ode Revisited: Is Carm. 1. 28. 32 Corrupt?. Issue 1 (1st January 2016) - Kraggerud, Egil
Abstract : The author offers line 32 in a new form reading debita iura vicesque supern ae (instead of the transmitted superb ae ): "due justice ( debita iura ) and heavenly retribution".